Genetic and molecular analyses for seed and oil yields improvement in Jatropha curcas L. populations - Khankahdani, Alireza Biabani (2012)
The current Jatropha improvement program was designed with the main objective to produce superior planting materials with high seed and oil yield production for commercial planting. The specific objectives were to study inter and intra-populations variation using morphological and Inter Simple Sequence Repeat (ISSR) molecular markers, to estimate genetic components, heritability values, general and specific combining abilities of several important characters for identifying the best parental lines and finally to quantify the level of heterosis for F1 hybrids in diallel crosses. Jatropha populations from Malaysia, Indonesia, India and Philippines were used as a base population in this selection program. Sixty four plants in each of six Jatropha populations, namely Malaysia1 (My1),Malaysia2 (My2), Indonesia1 (In1), Indonesia2 (In2), India1 (Id1) and Philippines1 (Ph1) were planted for field evaluation in Serdang University Agriculture Park,Universiti Putra Malaysia. Jatropha populations were arranged in a randomized complete block design (RCBD) with four replications at spacing of 4 m × 2 m. Analysis of variance in seed characters revealed that there was significant variation among Jatropha populations for seed length, seed width, seed weight and 100-seed weight at P ≤0.05.Population of My2 produced the highest oil content for both years (31.73 and 33.41%) of yield production. The lowest oil content was observed in population In1 for first and second years of harvesting (29.09 and 30.61%, respectively). Significant variation (P ≤ 0.05) was observed in plant height, number of secondary branches, days to flowering, number of inflorescences and seed yield. The highest seed yield was recorded in population In1 for first (46.5) and second year (222.8 g) in both years, whereas, the lowest was population In2 for first year and My1 for second year harvesting. Seed yield correlated significantly with days of flowering, number of inflorescences and plant height. Seed yield also correlated significantly with oil content. Days of flowering was found to have a high significantly positive relationship with plant height, number of secondary branches, number of tertiary branches, number of inflorescence, seed length and seed weight. The highest heritability was estimated for 100-seed weight (77.3%). The heritability values for plant height, number of secondary branch, days to flowering, seed weight, seed yield and oil content were 40.8, 47.8, 31.7,77.2, 52.0 and 49.7% respectively. ISSR markers were used to detect inter and intra-population variation of the based populations. The percentage of polymorphic bands for each population ranged from 46.15 to 60.84%, with an average of 55.10%. Among populations, the average number of alleles per locus (na) ranged from 1.46 (My1) to 1.61 (Ph1) with the mean number of 1.55, which the effective number of alleles per locus (ne) ranged from 1.12 (My1) to 1.17 (My2) with the mean number of 1.15. Among the populations, population My1 had the lowest genetic diversity levels, while population Ph1 showed the highest genetic diversity. The partitioning of genetic diversity into within population and between populations based on Shannon’s diversity index also revealed more variation within populations (0.81) than variations between populations (0.19). From the field evaluation of the Jatropha populations of 364 plants, ten superior individual plants (three from Malaysia, three Indonesia, two India and two Philippine population) were selected and were intercrossed in a half-diallel mating design (10×10) including selfed of each selected parental plants. The 45 F1 hybrids and 10 selfed progenies were evaluated in field using a randomized complete block design (RCBD) with three replications in Puchong University Agriculture Park, Universiti Putra Malaysia. Analyses of variance showed significant (P ≤ 0.01) variations among parents and hybrids for all characters. Analysis of variance for gene effects showed that both general (GCA) and specific combining ability (SCA) were influential for all traits. Analysis of specific combining ability in this study showed that a number of hybrids showed more precise for each character in different individual hybrids, but none showed the best SCA effect for all traits in one particular hybrid. The percentages of heterosis for traits in some hybrids were considerably high indicating that a high degree of genetic diversity among parents. High broad sense heritability was recorded for all traits. However, the ratios of GCA/SCA indicated that non-additive effects were more important than additive gene effects. The analyses of GCA did not show that any single parent was a high general combiner for all traits simultaneously.